Preoperative Maximization to Reduce Complications in Spinal Surgery. Issue 1 (January 2020) - Maitra, Sukanta; Mikhail, Christopher; Cho, Samuel K.; Daubs, Michael D.
Study design: Invited narrative review. Objectives: The aim of this review was to summarize current literature regarding risk factors that surgeons can optimize in the preoperative setting in the spinal surgery patient, in order to reduce complications and improve patient-reported outcomes. Methods: Review of the relevant literature by the authors. Results: Modifiable risk factors identified relative to the patient include obesity, malnutrition/nutrient deficiency, diabetes/hyperglycemia, preoperative anemia, vitamin D/DEXA (dual-energy radiograph absorptiometry), nicotine use/smoking, and opioid use/psychosocial factors. Conclusion: By maximizing a patient's physiological and psychological status prior to elective spine surgery, we may move closer to achieving the goals of value-based care: improving patient-reported outcomes while decreasing the cost of care.